Regulations on the Registration System of Marketing Affiliation Program on Electronic Contracts for Minors without Parental Consent - Alfaqiih, Abdurrahman; ., Nurjihad; Agus Riswandi, Budi; M.Ibrahim, Hanif (KnE Social Sciences, 2023)
Many of the participants of marketing affiliation programs are children, and their parents have not approved of their participation in the marketing affiliation program. This allegedly occurred because the information system of the application organizer in the affiliation program did not accommodate the alignment of legal requirements, which is one of the conditions for the validity of a contract. The purpose of this study is to normatively elaborate on the general practice of organizing marketing affiliation programs in Indonesia, particularly in identifying the legal loopholes for the program participants who happen to be underage and without parental permission. This study concluded that the registration system for marketing affiliation programs has loopholes that do not prevent participation in marketing affiliation programs by underage participants who do not have parental permission. Given that the loophole indirectly ignores the conditions of capacity, this will almost certainly affect the existence of electronic contracts agreed upon by the parties. Information system operators in marketing affiliation programs must create a more accommodating system to meet these legal requirements’ full scope. The system can be developed, particularly during the registration phase, so that the system has a filtering mechanism for immature registrants. As a result, changes to regulations governing electronic transaction practices are required to ensure that electronic transaction operators develop an electronic transaction system that meets the requirements for adult age limits and parental consent. Keywords: Affiliate Marketing, Electronic Contract, Minors, Parental Consent